Magnetic Behavior of Sintered NdFeB Magnets on a Long-Term Timescale - Minna Haavisto; Sampo Tuominen; Timo Santa-Nokki; Harri Kankaanpää; Martti Paju; Pekka Ruuskanen (Advances in Materials Science and Engineering)
Stable polarization of permanent magnets over the lifetime of the application is an important aspect in electrical machine design. Specification of the long-term stability of magnet material is difficult, since knowledge of the phenomenon is incomplete. To be able to optimize magnet material selection, the long-term magnetic behavior of the material must also be understood. This study shows that material with a very square JH curve is stable until a certain critical operating temperature is reached. Major losses are detected as the critical temperature is exceeded. Material with a rounder JH curve does not show a well-defined critical temperature, but increasing losses over a large temperature range. The critical temperature of a material is also dependent on the field conditions. Results differ whether the tests are performed in an open or closed magnetic circuit. In open-circuit tests, the opposing field is not homogeneously distributed throughout the volume of the magnet and thus the long-term behavior is different than that in closed-circuit conditions. Open-circuit tests seem to give bigger losses than closed-circuit tests in cases where the permeance coefficient of the open-circuit sample is considered to be the average permeance coefficient, calculated according to the dimensions of the magnet.